(untitled) (International Journal of Food and Nutritional Sciences, 2022)
There are two primary approaches to counteracting the harmful effects that mainstream pornography has on its audience: education and regulation. Analytic feminist philosophy has long included pornography as a central concern, although it has mostly concentrated on questions of regulation, especially on refuting arguments against it on the grounds that it ought to be considered free speech. Here, however, I examine some of the ways that philosophy might support an education-based strategy, namely the so called "education to address pornography’s influence." The main contribution of the paper is to argue that philosophical considerations can help shape the kind of content and messaging that such an education should have. Initially, I argue that philosophical considerations can help motivate this kind of overall approach to countering pornography’s influence.